GE_GERICHTE C/4243/2016 vom 15. Januar 2019 - GE Cour de justice (2019)
NOUVEAU MOYEN DE PREUVE ; NOTORIÉTÉ ; MANDAT ; RESPONSABILITÉ CONTRACTUELLE ; OBLIGATION D'ANNONCER(EN GÉNÉRAL) ; DILIGENCE | CO.394; CO.398.al1; CO.321a.al1